Loss of G(α12/13) exacerbates apical area dependence of actomyosin contractility - Xie, Shicong (Mol Biol Cell, 2016)
During development, coordinated cell shape changes alter tissue shape. In the Drosophila ventral furrow and other epithelia, apical constriction of hundreds of epithelial cells folds the tissue. Genes in the G(α12/13) pathway coordinate collective apical constriction, but the mechanism of coordination is poorly understood. Coupling live-cell imaging with a computational approach to identify contractile events, we discovered that differences in constriction behavior are biased by initial cell shape. Disrupting G(α12/13) exacerbates this relationship. Larger apical area is associated with delayed initiation of contractile pulses, lower apical E-cadherin and F-actin levels, and aberrantly mobile Rho-kinase structures. Our results suggest that loss of G(α12/13) disrupts apical actin cortex organization and pulse initiation in a size-dependent manner. We propose that G(α12/13) robustly organizes the apical cortex despite variation in apical area to ensure the timely initiation of contractile pulses in a tissue with heterogeneity in starting cell shape.